2022
DOI: 10.1155/2022/9764770
|View full text |Cite|
|
Sign up to set email alerts
|

A Meta-Analysis of the Influence of Tumor Necrosis Factor-α-308 Gene Polymorphism on Liver Cirrhosis

Abstract: Cirrhosis is an active hepatic inflammation process of the liver considered as the serious phase of different liver injuries. Epidemiological studies have evaluated the possible association between TNF-α-308G/A gene polymorphism and liver cirrhosis. In this study, we have furthered the study to assess the exact association of TNF-α-308G/A gene polymorphism with liver cirrhosis susceptibility by integrating all available data. Eligible case-control studies were carried out from the establishment of the project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In one recent meta-analysis of 22 studies incorporating 2,638 LC patients and 2,905 control individuals, the TNF-a -308A/G polymorphism was found to be unrelated to the risk of developing LC (20). No similar analyses, however, have been performed for the common rs361525 (-238 A>G) polymorphism in this gene or for the common IFN-g rs2430561 polymorphism (+874T/A).…”
Section: Introductionmentioning
confidence: 99%
“…In one recent meta-analysis of 22 studies incorporating 2,638 LC patients and 2,905 control individuals, the TNF-a -308A/G polymorphism was found to be unrelated to the risk of developing LC (20). No similar analyses, however, have been performed for the common rs361525 (-238 A>G) polymorphism in this gene or for the common IFN-g rs2430561 polymorphism (+874T/A).…”
Section: Introductionmentioning
confidence: 99%
“…So far, several common inflammatory factors gene polymorphisms in liver cirrhosis have been investigated by meta-analysis ( Chen et al, 2011 ; Guo et al, 2015 ; Guo et al, 2018 ; Zheng et al, 2021 ; Liu and Yang, 2022 ). However, to our knowledge, there has not been a systematic review and meta-analysis that has comprehensively assessed the association of inflammatory factors gene polymorphisms with liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%